THE EFFECT OF MODERNIZATION OF THE TAX ADMINISTRATION SYSTEM, TAX KNOWLEDGE, AND TAX SANCTIONS ON TAXPAYER COMPLIANCE AT PBJT ON FOOD AND/OR BEVERAGES IN CIMAHI CITY - Fridha Farhatunnisa; Anissa Yuniar Larasati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the effect of modernization of the tax administration system, tax knowledge, and tax sanctions on taxpayer compliance at PBJT on Food and/or Beverages in Cimahi City. The sample used in this study were PBJT taxpayers on food and/or beverages in Cimahi City. Data were collected using incidental sampling method. The number of questionnaires collected was 70 questionnaires out of 70 questionnaires distributed.This research was analyzed using multiple regression analysis models. The findings of this study indicate that the Modernization of the Tax Administration System partially affects the Compliance of PBJT Taxpayers on Food and / or Beverages in Cimahi City. Simultaneously, Modernization of Tax Administration System, Knowledge of Taxation, and Tax Sanctions affect the Compliance of PBJT Taxpayers on Food and/or Beverages in Cimahi City. There are interesting findings that tax knowledge and tax sanctions are not found to be independent variables that affect the compliance of PBJT taxpayers on Food and/or Beverages in Cimahi City.